LA REFLEXIÓN SOBRE EL FLÂNEUR Y LA FLANERIE EN LOS ESCRITORES MODERNISTAS LATINOAMERICANOS - Cuvardic García, Dorde (2012)
This article analyzes the flâneur (strolling spectator) poetics and the flanerie in the work of five Latin American modernist writers. As narrators, each one of them is conscious of and reflects about his behavior as flâneur and the tactics of flanerie or callejeo. Flanerie is interpreted as the gaze intellectuals use to understand the Turn of the Century city. The idle and indolent street strolling, ritual of the classic flâneur, is adopted in the writing of Enrique Gómez Carrillo, Julián del Casal, Amado Nervo o Manuel Gutiérrez Nájera.